2018
DOI: 10.1111/cmi.12860
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-induced susceptibility toCandida albicanssuper-infection in mice via monocyte methyltransferase Setdb2

Abstract: Systemic bacterial infections are prone to secondary Candida albicans super-infection. However, the molecular mechanisms involved remain poorly understood. In this study, a model comprising sublethal cecal ligation and puncture plus C. albicans intravenous injection was applied to mimic the situation in super-infection. Compared with mice without systemic bacterial infection, mice with systemic bacterial infection had lower antifungal gene expression (including Il1b, Tnf, Il6, Ifnb, Ifng, Cxcl1, and Ccr2) in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…The mice were more susceptible shortly after CLP rather than later on when the immune system was partially reconstituted [333]. In line with this, it was shown that monocytes from CLP-treated mice expressed less antifungal effector genes upon secondary intravenous C. albicans challenge, had less inflammatory monocytes in circulation, and less neutrophil influx into the kidneys [334]. In mice that received C. albicans via oral gavage a few hours after CLP, mortality was also increased as compared with CLP-treated animals [335].…”
Section: Fungal-bacterial Interactions—niche By Nichementioning
confidence: 96%
“…The mice were more susceptible shortly after CLP rather than later on when the immune system was partially reconstituted [333]. In line with this, it was shown that monocytes from CLP-treated mice expressed less antifungal effector genes upon secondary intravenous C. albicans challenge, had less inflammatory monocytes in circulation, and less neutrophil influx into the kidneys [334]. In mice that received C. albicans via oral gavage a few hours after CLP, mortality was also increased as compared with CLP-treated animals [335].…”
Section: Fungal-bacterial Interactions—niche By Nichementioning
confidence: 96%
“…The study showed that the weight of the mice in the TA combined with the FLC treatment group recovered, and the survival rate was significantly improved compared with the weight and survival rate of mice in the FLC group (P < 0.05). In addition, a comprehensive analysis of the kidney, the main target organ of invasive C. albicans, infection was also conducted (Chen et al, 2018). The results showed that the TA combined with the FLC treatment group had a significantly lower kidney fungal burden (P < 0.05), reduced number of lesions, and inflammatory cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…SETDB2 (CLLD8 or KMT1F) is a member of the histone H3K9 methyltransferase family-KMT1 sub-family, which includes SUV39H1, SUV39H2, G9a and SETDB1 [13][14][15]. SETDB2 plays important roles in immune system [15][16][17] and embryonic development [18,19]. In cancer research, SETDB2 has been found to be involved in cell cycle dysregulation in acute leukemia [20], associated with the prognosis and metastasis of renal tumors [21], and plays an oncogenic role in gastric cancer [22].…”
Section: Ivyspringmentioning
confidence: 99%